Characteristics and Influencing Factors of Intra-Dialysis Blood Pressure Variability in Hemodialysis Patients: A Retrospective Study - Xu H; Wang X; Feng M; Chen L (International Journal of General Medicine)
Haifan Xu,1,2,* Xiaoshuang Wang,1,3,* Miao Feng,1 Liqun Chen1 1Department of Nephrology, The First Affiliated Hospital of Chongqing Medical University, Chongqing, People’s Republic of China; 2Department of Nephrology, The People’s Hospital of Kaizhou District, Chongqing, People’s Republic of China; 3Department of Nephrology, Yubei District People’s Hospital, Chongqing, People’s Republic of China*These authors contributed equally to this workCorrespondence: Liqun Chen, Email cqll1970@163.comObjective: To investigate the correlation between background factors and blood pressure variability (BPV), and the prognostic value of intra-dialytic BPV metrics for cardiovascular death and all-cause mortality in hemodialysis (HD) patients.Methods: A retrospective study of 264 hD patients was followed up for 36 months. The intra-dialytic BP during the 3-month period for each patient was used to calculate BPV metrics, including standard deviation (SD), coefficient of variation (CV), average real variability (ARV), blood pressure change (ΔBP), and percent change in blood pressure (ΔBP/pre-BP). The primary outcomes were CVD death and all-cause mortality.Results: Age, body mass index (BMI), predialysis blood pressure, inter-dialytic weight gain rate (IDWG%), α- blockers, and cholesterol levels were positively correlated with intra-dialytic BPV. Hemoglobin and albumin are negatively associated with intra-dialytic BPV. In Cox regression analysis, SBP-ARV, ΔSBP, and ΔSBP/pre-SBP were independent risk factors for CVD death (HR: 1.087, 95% CI: 1.001– 1.181, p = 0.047; HR: 1.072, 95% CI: 1.016– 1.131, p = 0.011; HR: 1.107, 95% CI: 1.011– 1.211, p = 0.028). SBP-ARV showed the largest AUC of 0.593 (p = 0.022) in predicting all-cause death. SBP-ARV, ΔSBP, and ΔSBP/pre-SBP showed relatively large area (AUC = 0.631, 0.639, and 0.620; p = 0.007, 0.004, and 0.013 respectively) in predicting CVD death.Conclusion: Age, BMI, IDWG%, predialysis blood pressure, albumin, hemoglobin, α- blockers, and total cholesterol were significantly correlated with intra-dialytic BPV. SBP-ARV, ΔSBP, and ΔSBP/pre-SBP were independent risk factors for CVD mortality, and there were no differences in prognostic value among various BPV metrics.Keywords: hemodialysis, blood pressure variability, influencing factors, all-cause mortality, cardiovascular death